IMPLICATURE IN THE MADAGASCAR 2 MOVIE SCRIPT - Winda Safitri; Mu’man Mu’man (IKIP Siliwangi, 2022)
Pragmatics is part of the branches of linguistics, and in pragmatics we can learn implicatures. The purpose of this research is to analyze the dominant implicature and maxim violations contained in “Madagascar 2” movie script. This research used descriptive qualitative method, and the script was see from the internet. The type of implicature being studied is the conversational implicature. The conversational implicature arises because of the violation of one the four maxims, namely the maxim of quantity, maxim of quality, maxim of relationship, and maxim of the way. In this research, there were 25 implicatures ound from the movie script. The result is a quality maxim has 5 words, a maxim quantity has 9 words, a maxim relationship 7 words, and a maxim manner has 4 words. The implicature function is reflected in the purpose of the speech spoken by the speaker to the interlocutor during the conversation. Speech act are divided inti four, namely assertive, directive, commissive, and expressive. From the above results, the dominant function of the speech act implicature used in the film “Madagascar 2” is the implicature function of expressive speech acts. Keywords: Speech Acts, Implicature, Madagascar 2 Movie Script